Kesantunan Berbahasa dalam Novel Teman Imaji Karya Mutia Prawitasari: Kajian Pragmatik - Dewi Nur Fitriana (Academica: Journal of Multidisciplinary Studies, 2018)
AbstractIn literary works such as novels there are various aspects that attract the reader and make the reader enjoy it. The politeness aspect will be useful to help the reader in understanding the contents of the novel. In this study, the author examines the literary work of Teman Imaji's novel by Mutia Prawitasari which is analyzed in terms of the language approach, especially pragmatics, namely the theory of politeness principles. This paper aims to find out what politeness principles of language are contained in the novel of Teman Imaji by Mutia Prawitasari. The type of research used in this study is the literature. The texts examined in this study are in the form of literary novels, namely the novel Teman Imaji by Mutia Prawitasari. The method used in studying the novel Teman Imaji by Mutia Prawitasari is a descriptive analytic method. The results can be seen that in the novel there are several maxims which indicate the principle of language modesty. The maxims include wisdom maxim, generosity, praise, humility, agreement, and sympathy maxim.Keywords: Novel, politeness of language